2017
DOI: 10.12688/wellcomeopenres.10658.2
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial drugs and the prevalence of mental and neurological manifestations: A systematic review and meta-analysis

Abstract: Background: Antimalarial drugs affect the central nervous system, but it is difficult to differentiate the effect of these drugs from that of the malaria illness. We conducted a systematic review to determine the association between anti-malarial drugs and mental and neurological impairment in humans.  Methods: We systematically searched online databases, including Medline/PubMed, PsychoInfo, and Embase, for articles published up to 14th July 2016. Pooled prevalence, heterogeneity and factors associated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 91 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Considering that HCQ and chloroquine have similar pharmacological properties, their toxicity profiles could be considered comparable. A meta-analysis [ 44 ] and a pharmacovigilance study on registry [ 45 ] confirmed the association between HCQ and psychiatric events. The mechanisms responsible for the psychiatric ADRs following HCQ exposure are not fully clarified.…”
Section: Discussionmentioning
confidence: 98%
“…Considering that HCQ and chloroquine have similar pharmacological properties, their toxicity profiles could be considered comparable. A meta-analysis [ 44 ] and a pharmacovigilance study on registry [ 45 ] confirmed the association between HCQ and psychiatric events. The mechanisms responsible for the psychiatric ADRs following HCQ exposure are not fully clarified.…”
Section: Discussionmentioning
confidence: 98%
“…The most critical causes for discontinuation of MQ prophylaxis among travelers are ototoxic and neuropsychiatric adverse effects. The most typical adverse effects in malaria prophylaxis are headaches (15.5%) and dizziness (14.4%), with vertigo and visual difficulties reported in 1-10% of prophylactic users (69). In addition, a metaanalysis of 35 cohort studies (198,493 participants) comparing prophylactic MQ intake with placebo in adults, children and pregnant women indicated that MQ users were more likely to report nausea (high-certainty evidence) and dizziness (highcertainty evidence) (12).…”
Section: The Adverse Effects Of Antimalarials On the Vestibular Systemmentioning
confidence: 99%
“…Finally, in a meta-analysis of adverse event data from 51 studies involving quinoline and non-quinoline anti-malarials, primaquine at the labelled dose exhibited amongst the lowest risk of general neurologic and neuropsychiatric adverse events of all the anti-malarials evaluated [ 33 ].…”
Section: Aq Neurotoxicity In Humansmentioning
confidence: 99%